2022
DOI: 10.1038/s41598-022-11251-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of time-restricted feeding and type of food on fertility competence in female mice

Abstract: We assessed the effects of feeding regimen (ad libitum vs. time-restricted food access) and type of food (normal chow (NC: 12% fat) vs. moderately high calorie diet (mHCD: 31% fat)) on fertility competence of female mice. Mice fed mHCD had higher number of oocytes than mice fed NC. On the other hand, when mice were fed NC under time-restricted access to food (NT), the developmental rate to the blastocyst per number of normally fertilized ova was significantly decreased compared to others. The reactive oxygen s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Circadian disruption induced by other factors including chronically jetlag or genetic ablation of circadian genes was restored in mice treated with TRF (Chaix et al, 2019). However, TRF impaired fertility competence, which might be attributed to decreased serum lipids and increased oxidative stress in oocytes in mice (Konishi et al, 2022).…”
Section: Circadian Disruption and Endocrine Fgf Dysregulationmentioning
confidence: 95%
“…Circadian disruption induced by other factors including chronically jetlag or genetic ablation of circadian genes was restored in mice treated with TRF (Chaix et al, 2019). However, TRF impaired fertility competence, which might be attributed to decreased serum lipids and increased oxidative stress in oocytes in mice (Konishi et al, 2022).…”
Section: Circadian Disruption and Endocrine Fgf Dysregulationmentioning
confidence: 95%
“…To minimize the impact of variable factors on the results, researchers have turned to animal models. Experimental studies on mice with diet-induced obesity have confirmed an association between female obesity and reproductive disorders in the peri-conception period [5][6][7][8][9][10]. However, some of these studies produced inconsistent results as well.…”
Section: Introductionmentioning
confidence: 99%